Influence of in vitro IL-2 or IL-15 alone or in combination with Hsp-70-derived 14-mer peptide (TKD) on the expression of NK cell activatory and inhibitory receptors - Hromadnikova, Ilona; Pirkova, Petra; Sedlackova, Lucie (Mediators of inflammation, 2013)
NK cells represent a potential tool for adoptive immunotherapy against tumors. Membrane-bound Hsp70 acts as a tumor-specific marker enhancing NK cell activity. Using flow cytometry the effect of in vitro stimulation with IL-2 or IL-15 alone or in combination with Hsp70-derived 14-mer peptide (TKD) on cell surface expression of NK activatory receptors (CD16, NKG2D, NKG2C, NKp46, NKp44, NKp30, KIR2DL4, DNAM-1, and LAMP1) and NK inhibitory receptors (NKG2A, KIR2DL2/L3, LIR1/ILT-2, and NKR-P1A) in healthy individuals was studied. Results were expressed as the percentage of receptor expressing cells and the amount of receptor expressed by CD3(-)CD56(+) cellular population. CD94, NKG2D, NKp44, NKp30, KIR2DL4, DNAM-1, LAMP1, NKG2A, and NKR-P1A were upregulated after the stimulation with IL-2 or IL-15 alone or in combination with TKD. KIR2DL2/L3 was upregulated only by IL-15 and IL-15/TKD. Concurrently, an increase in a number of NK cells positive for CD94, NKp44, NKp30, KIR2DL4, and LAMP1 was observed. IL-15 and IL-15/TKD caused also cell number rise positive for KIR2DL2/L3 and NKR-P1A. Cell number positive for NKG2C and NKG2A was increased only by IL-2 and IL-2/TKD. The diverse effect of IL-2 or IL-15 w or w/o TKD on cell surface expression was observed in CD16, NKp46, and LIR1/ILT-2.
Keywords: proteiny tepelného šoku HSP70; NK Cell Lectin-Like Receptor Subfamily C; lektinové receptory NK-buněk - podrodina B; interleukin-2; buňky NK; receptor 3 spouštějící přirozenou cytotoxicitu; Antigens, Differentiation, T-Lymphocyte; NK Cell Lectin-Like Receptor Subfamily K; receptor 2 spouštějící přirozenou cytotoxicitu; Leukocytes, Mononuclear; lidé; T Lineage-Specific Activation Antigen 1; Natural Cytotoxicity Triggering Receptor 3; receptory IgG; lektinové receptory NK-buněk - podrodina C; receptory KIR2DL2; aktivační antigen 1 specifický pro T-buňky; Interleukin-2; kultivované buňky; Lysosomal Membrane Proteins; Humans; peptidy; Cells, Cultured; HSP70 Heat-Shock Proteins; Receptors, KIR2DL4; receptor 1 spouštějící přirozenou cytotoxicitu; Killer Cells, Natural; membránové glykoproteiny asociované s lyzozomy; Natural Cytotoxicity Triggering Receptor 2; interleukin-15; Receptors, IgG; lektinové receptory NK-buněk - podrodina K; diferenciační antigeny T-lymfocytů; Natural Cytotoxicity Triggering Receptor 1; Peptides; leukocyty mononukleární; Receptors, KIR2DL2; NK Cell Lectin-Like Receptor Subfamily B; Interleukin-15; receptory KIR2DL4